CSR Berbasis Komunitas dan Komunikasi Antar Budaya: Dalam Membangun Stakeholder Engagement - Anggraini, Choiria (Tuturlogi: Journal of Southeast Asian Communication, 2025)
This study examines the role of intercultural communication in the success of Corporate Social Responsibility (CSR) programs implemented by PT Danone Indonesia in two local communities: Desa Wisata Cibeusi and Kampung Adat Banceuy. In Indonesia’s multicultural setting, culturally sensitive communication is essential for building trust, strengthening stakeholder engagement, and ensuring program sustainability. Using a descriptive qualitative method with a case study approach, the research analyzes communication strategies, collaboration patterns, and the integration of corporate values such as transparency, inclusiveness, and integrity in CSR practices. Fieldwork was conducted from January 2024 to March 2025, involving interviews with CSR coordinators, local community leaders, and facilitators. The findings show that participatory and adaptive intercultural communication fosters co-creation, enhances community ownership, and contributes to corporate legitimacy. Communication across cultural boundaries allows companies to not only deliver information but also engage in dialogue that reflects local values, traditions, and aspirations. Furthermore, the study reveals that CSR programs incorporating cultural sensitivity create long-term harmonious relationships, mitigate potential social resistance, and encourage sustainable community empowerment. This research contributes theoretically by linking intercultural communication and stakeholder engagement while also providing practical insights for companies operating in culturally diverse societies to design CSR programs that are both inclusive and sustainable.